HOMONYM IN MANDAILING LANGUAGE - Rodiyah Harahap; Abdul Gapur (Kantor Bahasa Kepulauan Riau, 2020)
As a symbol of identity, pride, and support the development of Bahasa Indonesian, the study of the local language is required. One of them is Mandailing language, a local language with the majority of speakers in the area of Mandailing Natal Regency, Indonesia. This research deals with (1) what is the homonymy form in Mandailing language? (2) how is homonymy relation in Mandailing language. The objectives of this research are: (1) to explain homonymy forms in Mandailing language; (2) to describe homonymy relations in the Mandailing language. The research method used is descriptive qualitative. The data is oral data through key informants. Based on the analysis and discussion of data, it is known that (1) homonymy form in Mandailing language includes single form (free morpheme) and complex form (complex morpheme), (2) homonymy relations in Mandailing language include relations in two meanings and relations in three meanings.